Educational technology innovation during the COVID-19 pandemic - Alfath Rizq Denadi; Wafa Nabilah Sopyan (Curricula: Journal of Curriculum Development, 2022)
Innovations in education are continuously being made to continue learning when COVID-19 pandemic. One of solution for dealing with negative impact of pandemic in the domain of education is to innovate accompanied by technology or to innovate in the elements of learning to achieve educational and the learning goals. The purpose for this research is proposed as an overview of educational innovations in Indonesia during COVID-19 pandemic. This research use a descriptive research method and descriptive content analysis study. Research analysis is carried out on international articles, national articles, and other sources regarding learning solutions for the pandemic by making innovations in the field of educational technology. The use of technology in learning cannot be separated in distance learning for COVID-19 pandemic. Therefore, to solve the problem of education for this pandemic, innovations are made not only in the technology used in learning, but there needs to be innovation in the elements of learning to achieve educational goals during this pandemic.   Abstrak Inovasi dalam pendidikan terus dilakukan untuk melanjutkan pembelajaran pada masa pandemi COVID-19. Salah satu solusi untuk menangani dampak negatif dari pandemi dalam bidang pendidikan adalah dengan melakukan inovasi yang disertai oleh teknologi atau melakukan inovasi dalam unsur-unsur pembelajaran untuk mencapai tujuan pendidikan dan pembelajaran. Tujuan penelitian ini diajukan sebagai tinjauan umum terkait inovasi pendidikan di Indonesia pada masa pandemi COVID-19. Penelitian ini menggunakan metode descriptive research atau descriptive content analysis study. Analisis penelitian dilakukan pada artikel internasional, artikel nasional, maupun sumber lain mengenai solusi pembelajaran pada masa pandemi dengan melakukan inovasi di bidang teknologi pendidikan. Penggunaan teknologi dalam pembelajaran tidak dapat dipisahkan dalam pembelajaran jarak jauh di masa pandemi COVID-19. Maka dari itu, untuk menyelesaikan masalah pendidikan di masa pandemi ini, inovasi yang dilakukan tidak hanya dalam bidang teknologi yang dipakai dalam pembelajaran saja, tetapi perlu ada inovasi dalam unsur-unsur pembelajaran untuk tetap mencapai tujuan pendidikan pada masa pandemi ini. Kata Kunci: COVID-19; Inovasi; Pembelajaran; Teknologi Pendidikan